PEMBUATAN APLIKASI BAHAYA ROKOK BERBASIS ANDROID - Agung Wardoyo; Slamet Isworo (VISIKES: Jurnal Kesehatan Masyarakat, 2019)
An understanding of the dangers of cigarettes in Indonesian society has beenwidely carried out, both through online and offline, but often less effectivebecause the media used is less attractive and complicated in its use. This studyaims to make the media practical, interesting and easy to use by utilizing theandroid application of the dangers of mobile-based smoking online. Thisapplication is expected to be one of the interesting and easy ways to use to helpunderstand the dangers of smoking so that people can easily access thisapplication. Android-based mobile application uses the app inventor method,this application contains the notion of cigarettes, smoking habits and the dangersof smoking and the meaning of words and warning warnings contained incigarette packs. In this application, there are text, images, videos about thedangers of smoking, clinics stop smoking and videos about the dangers ofsmoking. Android-based applications are presented with easy to understand andapplicable, so this application can simplify and provide an explanation of smokingfor mobile phone users and it is expected that users who have a smoking habitwill realize and reduce and even stop smoking.Keywords: Media online, mobile phone, the dangers of smoking, android basedapplications, reduce smoking habits